A review on the deteriorating situation of smog and its preventive measures in Pakistan. (10th January 2021) - Raza, Waseem; Saeed, Saad; Saulat, Hammad; Gul, Hajera; Sarfraz, Muhammad; Sonne, Christian; Sohn, Z.-H.; Brown, Richard J.C.; Kim, Ki-Hyun
Abstract: Urbanization, industrialization, and increasing fossil fuel consumption are generally identified as the main contributors to poor air quality. Smog is a form of visible air pollution processes that can cause diverse health problems (e.g., pulmonary, respiratory, and skin diseases). In Lahore, the second-largest city of Pakistan, smog pollution has been a significant socioeconomic issue since 2013 of which situation has been worsening each year. In this systematic review, we discuss the major issues concerning smog in Pakistan: the causes, methods of detection, hazardous effects, and opportunities for preventive measures based on ground-level information. This study identifies smog as a potential source of human health risk as serious repercussions of economic development. It is thus suggested that adequate abatement measures should be established for the proper protection of public health.